2010
DOI: 10.1590/s0103-90162010000600008
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of rice cold tolerance at the seedling stage

Abstract: Rice (Oryza sativa L.) cold tolerance at the initial stages of development is a highly desirable trait to be incorporated into the state of Rio Grande do Sul, Brazil, cultivars, but selection for this trait must be performed under controlled temperature conditions, which limits the number of lines that can be evaluated. Knowledge of the inheritance of this trait is important to define breeding strategies. So the aim of this paper was to study the genetic basis of rice cold tolerance at the vegetative stage. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Petroline) primed in distilled water at 15 ºC, for 48 h, and assessed by different methods and storage periods, which have not presented advantage on percentage of seedlings in the field (Caseiro and Marcos-Filho, 2005). Likewise, for seeds of two different cultivars of cauliflower (Marcos-Filho and Kikuti, 2008) and cucumber (Gurgel-Junior et al, 2009) the priming did not change the percentage of germination, what emphasizes that this technique generally does not promote changes in germination percent , what is consistent with data found in the literature. There was statistically significant reduction on germination percent of the seeds, when the period of osmotic priming with potassium nitrate has been increased to all treatments assessed (Table 1).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Petroline) primed in distilled water at 15 ºC, for 48 h, and assessed by different methods and storage periods, which have not presented advantage on percentage of seedlings in the field (Caseiro and Marcos-Filho, 2005). Likewise, for seeds of two different cultivars of cauliflower (Marcos-Filho and Kikuti, 2008) and cucumber (Gurgel-Junior et al, 2009) the priming did not change the percentage of germination, what emphasizes that this technique generally does not promote changes in germination percent , what is consistent with data found in the literature. There was statistically significant reduction on germination percent of the seeds, when the period of osmotic priming with potassium nitrate has been increased to all treatments assessed (Table 1).…”
Section: Resultssupporting
confidence: 89%
“…Cold tolerance is a characteristic highly desirable for the rice genotypes to be grown in the south of country (Cruz et al, 2010). However, the origin of most cultivars commercially used in that region is tropical, what largely contributes to reduction of productivity of rice crop in the state of Rio Grande do Sul (Mertz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some subtropical regions such as Brazil (comprising approximately 1 million ha of rice), cold stress at the vegetative stage accounts for up to a 20% yield loss (Cruz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Not only the sign of SCA value, also the magnitude of the value is meaningful. It was suggested that the high magnitude means high genetic divergence and high heterosis in the hybrids [32]. In addition, hybrids displaying heterosis are said to have favorable combining ability [13].…”
Section: Discussionmentioning
confidence: 99%